Load flexibility potential across residential, commercial and industrial sectors in Brazil - Dranka, Geremi Gilson (2020)
The flexibility in grid operations has become a valuable solution to respond to the several problems brought about by the growth of intermittent renewable generation. The use of Demand Response (DR) measures has emerged as a promising option to tackle these challenges. However, to the best of the authors' knowledge, the assessment of the theoretical DR potential has not yet been fully addressed in the available literature. This paper presents a first attempt to establish the theoretical load flexibility potential for the Brazilian power sector and includes two central issues: (1) a sectoral assessment across the residential, commercial and industrial sectors and (2) a regional analysis by broadly splitting up the Brazilian power system into four main subsystems. Our findings reveal that the overall maximum hourly theoretical DR potential in Brazil is expected to double, increasing from 12.8 GW in 2017 to almost 25.6 GW by 2050. Although the majority of the demand-side response potential seems to lie in the industrial sector, a lower but still substantial potential for the residential and commercial sectors has been also identified. The evidence from this study supports the hypothesis that the commercial sector will have a key role in offering the most valuable load flexibility potential (i.e. when the power system mostly needs). The high expected increase in the overall electricity DR potential for the residential sector is driven mainly by the increase in both the number of households and the number of appliances per house. However, large amounts of flexible loads in the residential sector might not be necessarily available during on-peak times. Findings of this research may be of great assistance for future analyses to identify, for example, the extent to which DR can cost-effectively compete with other supply-side options. (C) 2020 Elsevier Ltd. All rights reserved.